1998
DOI: 10.1128/jvi.72.9.7697-7702.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleolus Is the Site of Borna Disease Virus RNA Transcription and Replication

Abstract: Borna disease virus (BDV) is a neurotropic nonsegmented negative-strand RNA virus with limited homology to rhabdoviruses and paramyxoviruses. A distinguishing feature of BDV is that it replicates in the nucleus of infected cells. Strand-specific probes used for in situ hybridization of infected rat brain showed that there was differential localization of positive- and negative-strand RNAs within the nucleus of neurons. Within nuclei, sense-strand RNAs were preferentially localized within nucleolar regions whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 37 publications
0
30
0
1
Order By: Relevance
“…Exogenous non-ribosomal proteins have been demonstrated to be transported to the nucleolus under certain conditions. Proteins from porcine reproductive and respiratory syndrome virus (Rowland et al, 1999), Semliki Forest virus (Favre et al, 1994), coronavirus (Hiscox et al, 2001), and Borna disease virus (Pyper et al, 1998) have been reported to localize in the nucleolus and be involved in various aspects of virus replication. A cluster of basic amino acids is responsible for targeting proteins to the nucleus or nucleolus (Kaffman and O'Shea, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous non-ribosomal proteins have been demonstrated to be transported to the nucleolus under certain conditions. Proteins from porcine reproductive and respiratory syndrome virus (Rowland et al, 1999), Semliki Forest virus (Favre et al, 1994), coronavirus (Hiscox et al, 2001), and Borna disease virus (Pyper et al, 1998) have been reported to localize in the nucleolus and be involved in various aspects of virus replication. A cluster of basic amino acids is responsible for targeting proteins to the nucleus or nucleolus (Kaffman and O'Shea, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Another animal virus, the (À)ssRNA containing Borna disease virus, uses the nucleolus as a site of genome replication (Pyper et al, 1998). An RNA-binding protein encoded by this virus has the appropriate trafficking signals for import and export to and from the nucleus (Cros and Palese, 2003)…”
Section: A Viruses That Replicate In the Nucleusmentioning
confidence: 99%
“…A number of virus proteins have been shown to localize to nucleolus and dysregulated nucleolar functions for virus replication, including human immunodeficiency virus (HIV) type I Rev and Tat (Strebel, 2003), human T-cell leukemia virus (HTLV) Rex (Kubota et al, 1996), and herpes simplex virus (HSV) type 1 gamma (1) 34.5 protein (Cheng et al, 2002). The nucleolus is also the site of Borna disease virus replication and transcription (Pyper et al, 1998). Coronavirus was known to replicate and assembled in the cytoplasm.…”
Section: Determination Of the Nucleolar Localization Signals Of Protementioning
confidence: 99%